Pembelajaran PAI Berbasis ICT DI SD Swasta Yayasan Pendidikan Shafiyyatul Amaliyyah Medan - Syafaruddin Siahaan; Amiruddin ms; Sodri Daulay (Tazkir : Jurnal Penelitian Ilmu-ilmu Sosial dan Keislaman, 2020)
This study aims to determine: 1. ICT-based PAI Learning Planning in Private Islamic Education Foundation Shafiyyatul Amaliyyah International Islamic Full Day School Medan, 2. The use of ICT in PAI learning in Private Islamic Education Foundation Shafiyyatul Amaliyyah International Islamic Education Full Day School Medan, and 3. Problems in the implementation of ICT-based PAI learning and the solution at the Private Islamic Education Foundation Shafiyyatul Amaliyyah International Islamic Full Day School Medan. This research is includes as field research. The technique used in collecting this research data uses interview, observation, and documentation techniques. Then in the analysis of data using descriptive qualitative methods, the data collected is then analyzed so that it becomes a conclusive unity using the inductive approach. From the results of research in general shows that the implementation of ICT-based learning in the Private Foundation Education Foundation Shafiyyatul Amaliyyah International Islamic Full Day School Medan can be said to be good. This can be seen from the learning objectives of PAI at the school that do not deviate from the goals of national education and the results of the evaluation exceed the KKM standard (Minimum Completeness Criteria) of Islamic Religious Education learning